Should We Cheer Together? Gender Differences in Instantaneous Well-Being during Joint and Solo Activities - J. Ignacio Gimenez-Nadal; José Alberto Molina; Jorge Velilla (Institute of Labor Economics (IZA), 2020)
The COVID-19 pandemic has confined millions in their homes, representing an unprecedented case for spending more time together with family members. This situation is a challenge for households, given that more time with the partner or children may not necessarily translate into increased well-being. This paper explores subjective well-being in the uses of time for US and UK workers, differentiating between solo activities and activities done with family members. Using the American and British time use surveys, we compute the instant utility associated with paid work, unpaid work, leisure, and childcare activities. The results show that workers prefer joint leisure to solo leisure, and significant differences exist between female and male workers for solo and joint market work and housework. The conclusions of this paper indicate that there are gender differences in the effects of the COVID-19 pandemic on well-being, affecting the time spent by individuals in both paid and unpaid work.
Keywords: D10; J16; J22; 330; time allocation; instantaneous well-being; togetherness; gender difference; COVID-19